2019
DOI: 10.1128/aac.00705-19
|View full text |Cite
|
Sign up to set email alerts
|

Verapamil Improves the Activity of Bedaquiline against Mycobacterium abscessusIn Vitro and in Macrophages

Abstract: Due to intrinsic multidrug resistance, pulmonary infections with Mycobacterium abscessus are extremely difficult to treat. Previously, we demonstrated that bedaquiline is highly effective against Mycobacterium abscessus both in vitro and in vivo. Here, we report that verapamil improves the efficacy of bedaquiline activity against M. abscessus clinical isolates and low-level resistant strains, both in vitro and in macrophages. Verapamil may have clinical potential as adjunctive therapy provided that sufficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Several reports showed that the most spreading mechanism of BDQ resistance in clinical setting is represented by mutations in Rv0678 gene even if with a low level of BDQ-resistance (Villellas et al, 2017;Nieto Ramirez et al, 2020). To fight BDQ-resistance caused by Rv0678 mutations and to allow its use for the largest possible part of patients, verapamil, an efflux inhibitor, could be the keystone, since it has been demonstrated to increase the efficacy of BDQ against both M. tuberculosis and Mycobacterium abscessus (Ghajavand et al, 2019;Viljoen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports showed that the most spreading mechanism of BDQ resistance in clinical setting is represented by mutations in Rv0678 gene even if with a low level of BDQ-resistance (Villellas et al, 2017;Nieto Ramirez et al, 2020). To fight BDQ-resistance caused by Rv0678 mutations and to allow its use for the largest possible part of patients, verapamil, an efflux inhibitor, could be the keystone, since it has been demonstrated to increase the efficacy of BDQ against both M. tuberculosis and Mycobacterium abscessus (Ghajavand et al, 2019;Viljoen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium antagonists improved in vitro activities of tetracycline and fluoroquinolones against S. aureus, Enterobacteriaceae and non-fermenters irrespective of whether the strains were tetracycline-or fluoroquinolone-resistant [158][159][160]. It also improved activities of ofloxacin, rifampicin, and bedaquilin, but not isoniazid or amikacin against M. tuberculosis as well as M. abscessus (Table 3) [ [161][162][163][164][165][166][167][168][169]. Verapamil also increased the intraphagocytic activities of isoniazid and rifampicin [168] as well as bedaquilin and moxifloxacin [168] against drug-susceptible and drug-resistant M. tuberculosis and also the intracellular activity of azithromycin against L. monocytogenes [170,171] and that of daptomycin against S. aureus [172].…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…Two studies reported poor or negative results for BDQ administration against nontuberculous mycobacteria-infected patients (27,28). However, recent studies showed that the activity of BDQ can be potentiated with adjunctive therapy, thus improving BDQ-based treatments (16,29). This study provides evidence that treatment with the BDQ-IPM combination remains superior to treatment with IPM alone and equivalent to that with BDQ alone, as judged by the comparable bacterial clearance in the spleens of the mice treated with BDQ-IPM versus BDQ alone.…”
mentioning
confidence: 99%